MicroRNA Alterations in Chronic Traumatic Encephalopathy and Amyotrophic Lateral Sclerosis - Alvia, Marcela; Aytan, Nurgul; Spencer, Keith R.; Foster, Zachariah W.; Rauf, Nazifa Abdul; Guilderson, Latease; Robey, Ian; Averill, James G.; Walker, Sean E.; Alvarez, Victor E.; Huber, Bertrand R.; Mathais, Rebecca; et al. (Frontiers in Neuroscience, 2022)
Repetitive head impacts (RHI) and traumatic brain injuries are risk factors for the neurodegenerative diseases chronic traumatic encephalopathy (CTE) and amyotrophic lateral sclerosis (ALS). ALS and CTE are distinct disorders, yet in some instances, share pathology, affect similar brain regions, and occur together. The pathways involved and biomarkers for diagnosis of both diseases are largely unknown. MicroRNAs (miRNAs) involved in gene regulation may be altered in neurodegeneration and be useful as stable biomarkers. Thus, we set out to determine associations between miRNA levels and disease state within the prefrontal cortex in a group of brain donors with CTE, ALS, CTE + ALS and controls. Of 47 miRNAs previously implicated in neurological disease and tested here, 28 (60%) were significantly different between pathology groups. Of these, 21 (75%) were upregulated in both ALS and CTE, including miRNAs involved in inflammatory, apoptotic, and cell growth/differentiation pathways. The most significant change occurred in miR-10b, which was significantly increased in ALS, but not CTE or CTE + ALS. Overall, we found patterns of miRNA expression that are common and unique to CTE and ALS and that suggest shared and distinct mechanisms of pathogenesis.